Functional outcome of peritrochanteric fractures femur treated with proximal femoral nail - T., Binay Gowda; M. D., Chunchesh; Ahuja, Vani; K. , Sushan (International Journal of Research in Orthopaedics, 2025)
Background: Peritrochanteric fractures are common injuries, especially in the elderly, with significant impact on health care. The aim of treatment should be prevention of malunion and early mobilization. Taking all the factors into consideration, surgery by internal fixation of the fracture is an ideal choice. Methods: This study included 40 adult patients with peritrochanteric fractures of the femur who met the inclusion criteria and were treated with a Proximal Femoral Nail at BGS Global Institute of Medical Sciences, Bangalore, from November 2022 to November 2024. Results: The study included 40 cases, 31 males and 9 females, aged 22–94. The majority of patients (45%) were admitted for slip-and-fall injuries, mostly right-sided fractures. 25 of 40 cases were trochanteric, 15 subtrochanteric. The trochanteric fracture group had 40% Boyd and Griffin type 2, while the subtrochanteric group had 33.3% Seinsheimer type IIIa and 20% type IIb. The average hospital stay was 20.67 days and weight-bearing took 16.5 weeks. Two patients died before the 6-week follow-up and three were lost to follow-up. The remaining 35 fractures were 22 trochanteric and 13 subtrochanteric. 90.9% of trochanteric fractures and 88.57% of subtrochanteric fractures had good to excellent results. Conclusions: The study concludes that the PFN is an excellent implant for the treatment of peritrochanteric fractures. The terms of a successful outcome include a thorough understanding of fracture biomechanics, proper patient selection, good preoperative planning, accurate reduction of the fracture, instrumentation and a good image intensifier.